A Visual Semiotic Analysis On Webtoon True Beauty - Cindy Pratiwi; Muhizar Muchtar; Alemina Br. Perangin-Angin (ITScience (Information Technology and Science), 2022)
This research is aimed to identify the signs in the webtoon True Beauty and aim to interpret the meaning of signs in the webtoon True Beauty by using Charles Sanders Pierce’s triadic theory. This research is applied the qualitative method. The data source in this research are the webtoon True Beauty. In collecting the data, researchers need to download the True Beauty webtoon to get softcopy data, then researchers take several panels from the selected True Beauty webtoon episodes. There are five data analyzed from the 149th episode of the webtoon True Beauty and each data of consists of the sign and interpreting meaning. The signs found on webtoon True Beauty consisted of representamen (legisign), object (icon), and interpretant (rheme) and there are three steps to interpreting the meaning of signs that are found on webtoon True Beauty, they are non-verbal communicative legisign, framing techniques, and communicative act.